2022
DOI: 10.1111/sjop.12856
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences in patients with severe health anxiety: No evidence for an increased frequency compared to patients with obsessive–compulsive disorder

Abstract: Theoretical models of health anxiety emphasize adverse childhood experiences in the development of the disorder, but few studies examine such events in patients with severe health anxiety and the results are difficult to compare across studies. The present study examined adult retrospective reports of illness‐related and traumatic childhood experiences in 31 patients with severe health anxiety, 32 non‐clinical control participants, and a clinical control group of 33 patients with obsessive–compulsive disorder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Traumatic experiences in childhood will affect the child’s personality development and emotional regulatory ability and may lead to adverse cognitive patterns, resulting in excessive responsibility and perfectionism, difficulty coping with negative emotions and pressure, and unhealthy defense mechanisms to relieve anxiety or guilt with the help of compulsive behavior. 39 , 40 Many studies have shown that traumatic experiences in childhood damage individuals’ physical health and are closely related to adult mental disorders. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Traumatic experiences in childhood will affect the child’s personality development and emotional regulatory ability and may lead to adverse cognitive patterns, resulting in excessive responsibility and perfectionism, difficulty coping with negative emotions and pressure, and unhealthy defense mechanisms to relieve anxiety or guilt with the help of compulsive behavior. 39 , 40 Many studies have shown that traumatic experiences in childhood damage individuals’ physical health and are closely related to adult mental disorders. 41 …”
Section: Discussionmentioning
confidence: 99%